Neuroendocrine Tumors of the Lung: Hystological Classification, Diagnosis, Traditional and New Therapeutic Approaches - Cueto, A.; Burigana, F.; Nicolini, A.; Lugnani, F. (Current Medicinal Chemistry, 2014)
Lung neuroendocrine tumors are neoplasms originating from bronchopulmonary neuroendocrine cells, usually Kulchitsky cells, loaded with argentaffin granules. They account for 20-25% of all primitive lung tumors, the most common being the small-cell undifferentiated carcinoma. They include different tumors, from tumors of low-grade malignancy, especially the typical carcinoids, with high survival rates after surgical therapy, to the high-grade malignancy tumors, especially small-cell undifferentiated carcinomas. The latter have very few indications for surgical treatment with a low survival rate, even after multimodal therapy. The aim of this review is to describe the present knowledge and discuss possible new developments in the management of pulmonary neuroendocrine tumors. The authors examine and discuss in particular the role that surgical techniques should have in the treatment of small-cell lung cancer in opposition to a nihilism position that has limited therapies to non-surgical approaches. The critical review of this attitude opens the door to a more aggressive approach. In the meantime the review shows that it might be possible to include the new minimally invasive percutaneous ablative techniques as cryosurgery, thermotherapy and irreversible electroporation within a modern and flexible framework. The authors also present the hypothesis that cancer stem cells (CSC) are at the basis of recurrences of small-cell lung cancer (SCLC) and therefore that the issue is of difficult solution with the conventional oncologic approach considering the chemo-resistance of CSC to drugs. For these reasons an epigenetic therapy based on differentiation factors is proposed alongside the usual surgical and chemo-radiation protocols.
Keywords: carcinoid tumor